2020
DOI: 10.1103/physrevresearch.2.032039
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of localized and extended phases: Many-body localization in a harmonic trap

Abstract: We show that the presence of a harmonic trap may in itself lead to many-body localization for cold atoms confined in that trap in a quasi-one-dimensional geometry. Specifically, the coexistence of delocalized phase in the center of the trap with localized region closer to the edges is predicted with the borderline dependent on the curvature of the trap. The phenomenon, similar in its origin to Stark localization, should be directly observed with cold atomic species. We discuss both the spinless and the spinful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 54 publications
(89 reference statements)
6
37
0
Order By: Relevance
“…First we briefly recall the model and study the time dynamics in the presence of random disorder. Later we consider localization in disorder-free tilted lattice that extends extensive recent studies of such models [51][52][53][54][55][56][57] to infinite range potentials. Let us also note here the recent work [58] which discusses localization in tilted lattice for dipolar i.e., power-law decaying interactions.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…First we briefly recall the model and study the time dynamics in the presence of random disorder. Later we consider localization in disorder-free tilted lattice that extends extensive recent studies of such models [51][52][53][54][55][56][57] to infinite range potentials. Let us also note here the recent work [58] which discusses localization in tilted lattice for dipolar i.e., power-law decaying interactions.…”
Section: Introductionmentioning
confidence: 92%
“…As a second example we consider the case of a harmonic potential on top of the lattice, h i = A 2 (i − i 0 ) 2 , where i 0 denotes the center of the lattice (i 0 = 20.5 for lattice of size L = 40 considered). Such a potential was considered in [54] where we have found that for short-ranged interactions the system splits into separate regions. While at the center the system delocalizes, clear signatures of localization are observed at the outer regions leading to "phase separation" or the coexistence of localized phases with ergodic central bubble.…”
Section: Disorder-free Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, a substantial fraction of states in other subspaces are delocalized [38]. Coexistence of localization and delocalization has been demonstrated in a variety of systems with dipole (or higher) moment conservation both numerically [38][39][40][41][42][43][44] and analytically [38,45]. Experimental evidences for the Wannier-Stark localization without disorder were recently reported [1,2,46].…”
Section: Since the Pioneering Work Of Kagan And Maksymovmentioning
confidence: 99%